A comparison study of the fresh and hardened properties of normal weight and lightweight aggregate concretes - Shafigh, Payam; Lee, Jin Chai; Mahmud, Hilmi; Nomeli, Mohammad A. (Elsevier, 2018)
This study compares the engineering properties of normal weight concrete with those of concrete with two types of lightweight aggregates, namely, oil-palm-boiler-clinker (OPBC) concrete and lightweight expanded clay aggregate (LECA) concrete. OPBC is a porous solid waste from the palm oil industry, while LECA is an artificial and impenetrable material. The conventional coarse aggregates in a high-strength normal weight concrete were replaced by each of these lightweight aggregates, and the effect of such substitution on the fresh and hardened properties of the concrete was studied. The test results revealed that the OPBC concrete outperforms the LECA concrete in terms of workability, mechanical properties, and specific strength. The LECA concrete achieved its ceiling strength in 7 days, while the OPBC concrete still had strength gain by time. The LECA concrete demonstrated a greater drying shrinkage than both the normal weight and OPBC lightweight concretes between 14 days and 90 days. The use of OPBC must therefore be promoted to produce a cleaner and greener concrete that can benefit the construction and agricultural industries.